In vivo reflectance confocal microscopy features of a melanoacanthoma - Neda Shahrian; Jane M. Grant-Kels; Harold S. Rabinovitz; Margaret Oliviero; Alon Scope (Mattioli1885, 2016)
Efforts have been expended to evaluate the reflectance confocal microscopy (RCM) features of different clinical entities in order to more thoroughly delineate benign versus malignant features. In this way, RCM can help clinicians to be more selective in regard to undertaking appropriate skin biopsies and improving their benign to malignant ratio. Herein, we report a case of a histopathologically proven melanoacanthoma, a variant of seborrheic keratosis. There are scarce reports describing the RCM features of melanoacanthoma. Our case demonstrated RCM features that were suspicious for melanoma. More RCM images of this benign entity are needed to establish definitive diagnostic criteria.